PENEGAKAN HUKUM TERHADAP PEROKOK PADA KAWASAN TERBATAS ROKOK DI PASAR TRADISIONAL KREMPYENG GRESIK - Najamuddin, Alif (Universitas Negeri Surabaya, 2020)
Gresik Regency Regulation Number 4 of 2015 concerning Non-Smoking and Non-Smoking Areas has been in effect for 5 (five) years. But the fact is that there are still many violations found in areas designated as non-smoking areas, especially in the traditional Gresik market. The majority of smokers are traders and workers in these market areas. There is no special place for smoking inside this traditional market, so cigarette smoke rises in the market area which certainly disturbs buyers and other traders as passive smokers. In this regard, the writer identifies that in its application Article 13 Letter B of the Regional Regulation of Gresik Regency Number 4 of 2015 concerning Non-Smoking Zones and Cigarette-Restricted Areas Related to Cigarette-Restricted Areas in Gresik Traditional Market, this has not proceeded accordingly, so the authors are interested in writing related how enforcement and barriers experienced in enforcing local regulations Gresik Regency Regulation Number 4 of 2015 concerning No-Smoking Areas and Restricted-Smoking Areas. This study aims to determine how law enforcement against smokers in cigarette-restricted areas in the Krempyeng Gresik Traditional Market and to determine the obstacles faced in law enforcement against smokers in cigarette-restricted areas in the Krempyeng Gresik Traditional Market. This research is a type of empirical juridical research located in Krempeyeng Market in Gresik Regency and Satpol PP in Gresik Regency. The data used are primary and secondary data obtained from interviews, literature studies, journals, research results, websites, and statutory regulations. Data collection is done through interviews and documentation. Data processing is done by checking information and classified systematically, as well as processing primary and secondary data relations. The results of data processing were analyzed descriptively qualitatively. The results of the study showed that law enforcement related to the implementation of Gresik Regency Regulation Number 4 Year 2015 Regarding No-Smoking Areas and Restricted-Smoking Areas in the Krempyeng Market area of Gresik Regency was still lacking. The Market Management Unit of the Gresik Regency Cooperative, Micro Business and Industry and Trade Office as the official in charge of creating a smoking room considers it unnecessary. The Gresik Regency Civil Service Police Office has not made any appeal or given administrative sanctions to smokers in the limited smoking area in the Grempik Krempyeng Market. The culture of the people who are less concerned about the dangers of smoking and the prohibition of smoking in the limited smoking area makes the Regional Regulation of Gresik Regency Number 4 Year 2015 Regarding No-Smoking Areas and Restricted-Smoking Areas not being able to apply optimally in the Krempyeng Market area of Gresik Regency.. Keyword: Law Enforcement, Restricted Area of Cigarettes, Traditional Market.Â